2015
DOI: 10.1111/coep.12122
|View full text |Cite
|
Sign up to set email alerts
|

Old Wine in a New Bottle: Trade Openness and Fdi Flows—are the Emerging Economies Converging?

Abstract: This study uses the club convergence methodology of Phillips and Sul (2007) for emerging economies spanning the period 1960-2013 to explore whether such convergence exists and whether the increase of international trade and foreign direct investment (FDI) flows has been a global or club phenomenon. We find the absence of a homogeneous convergence club. The results for FDI outflows also reach similar conclusions, suggesting the formation of convergence clubs by stage of development. These results suggest that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
2
0
1
Order By: Relevance
“…The methodological advantages of the Phillips and Sul (2007) method allows it to be used in researching convergence clubs in different areas such as energy consumption, happiness, military spending, etc. (Kourtzidis et al (2018), Panopoulou and Pantelidis (2009), Apergis and Cooray (2016), Ivanovski et al (2018), Georgellis (2013) Saba andNgepah, (2021)).…”
Section: Methodsmentioning
confidence: 99%
“…The methodological advantages of the Phillips and Sul (2007) method allows it to be used in researching convergence clubs in different areas such as energy consumption, happiness, military spending, etc. (Kourtzidis et al (2018), Panopoulou and Pantelidis (2009), Apergis and Cooray (2016), Ivanovski et al (2018), Georgellis (2013) Saba andNgepah, (2021)).…”
Section: Methodsmentioning
confidence: 99%
“…Literatürde genel olarak araştırılan çalışmalara bakıldığında uluslararası ticaretin yakınsama etkilerinin incelendiği görülmektedir. Yakınsama analizinin tespitinde genellikle birim kök testlerinden yararlanılmaktadır (Apergis & Cooray, 2016;Ben-David, 1993;Ben-David, 1996;Ben-David & Kimhi, 2000;Choi, 2009;Sachs & Warner, 1995). Bu amaçla çalışmada seçilmiş Orta Doğu Ülkelerinde (İsrail, Lübnan, İran, Mısır, Ürdün ve Türkiye) 1989-2021 dönemi arasında dış ticarette yakınsamanın olup olmadığı araştırılmıştır.…”
Section: Veri Seti Ve Analizunclassified
“…In other words, the studies in the literature have focused on determining whether free trade causes convergence of countries' incomes. In testing the convergence hypothesis, mostly panel unit root tests were used Apergis and Cooray (2016) conducted a convergence analysis by classifying countries according to their trade openness degrees using the Phillips and Sul (2007) method. Empirical findings on trade openness revealed that the countries participating in the analysis did not create a homogeneous convergence club.…”
mentioning
confidence: 99%